A Critical Assessment of the Microorganisms Proposed to be Important to Enhanced Biological Phosphorus Removal in Full-Scale Wastewater Treatment Systems - Stokholm-Bjerregaard, Mikkel; McIlroy, Simon J.; Nierychlo, Marta; Karst, Søren M.; Albertsen, Mads; Nielsen, Per H. (Frontiers in Microbiology, 2017)
Understanding the microbiology of phosphorus (P) removal is considered essential to knowledge-based optimization of enhanced biological phosphorus removal (EBPR) systems. Biological phosphorus removal is achieved in these systems by promoting the growth of organisms collectively known as the polyphosphate accumulating organisms (PAO). Also considered important to EBPR are the glycogen accumulating organisms (GAO), which are theorized to compete with the PAO for resources at the expense of P removal efficiency. Numerous studies have sought to identify the PAO and their GAO competitors, with several candidates proposed for each over the last few decades. The current study collectively assessed the abundance and diversity of all proposed PAO and GAO in 18 Danish full-scale wastewater treatment plants with well-working biological nutrient removal over a period of 9 years using 16S rRNA gene amplicon sequencing. The microbial community structure in all plants was relatively stable over time. Evidence for the role of the proposed PAO and GAO in EBPR varies and is critically assessed, in light of their calculated amplicon abundances, to indicate which of these are important in full-scale systems. Bacteria from the genus Tetrasphaera were the most abundant of the PAO. The “Ca. Accumulibacter” PAOs were in much lower abundance and appear to be biased by the amplicon based method applied. The genera Dechloromonas, Microlunatus, and Tessaracoccus were identified as abundant putative PAO that require further research attention. Interestingly, the actinobacterial Micropruina and sbr-gs28 phylotypes were among the most abundant of the putative GAO. Members of the genera Defluviicoccus, Propionivibrio, the family Competibacteraceae, and the spb280 group were also relatively abundant in some plants. Despite observed high abundances of GAO (periodically exceeding 20% of the amplicon reads), P removal performance was maintained, indicating that these organisms were not outcompeting the PAO in these EBPR systems. Phylogenetic diversity within each of the PAO and GAO genera was observed, which is consistent with reported metabolic diversity for these. Whether or not key traits can be assigned to sub-genus level clades requires further investigation.